A Qur'anic Concept of Sadness: Implication for CBT-Q Content Supplement (Part 1) - Nur Afifah Abas (Universitas Islam Negeri Mataram, 2021)
This study develops a Qur’anic culturally-adapted psychoeducational content supplement on sadness (ḥuzn) for the Cognitive Behavioral Therapy (CBT) Approach in preventing or treating depression among Muslim clients. The content of the concept derived from a Qur’anic Thematic Exegetical Analysis (al-Tafsīr al-Mawḍu’ī). It is a support towards religious psychotherapy from the Islamic Studies field. CBT approach is compatible with the religion of Islam provided complying with the Islamic methodologies e.g., the epistemological aspects of constructs/absolute or relative reality. It is educationally important for Muslims’ existential needs to resiliently face the challenges of life in general.